Building on CORAF’s scaling mechanisms to spillover climate-smart agriculture technologies and innovations in West and Central Africa - Kpadonou, G Esaïe; Ganyo, Komla Kyky; Lamien, Niéyidouba; Sobgui, Caroline Makamto; Segnon, Alcade C; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
CORAF’s conceptual approach for scaling-up Technologies and Innovations (T&Is) across West & Central Africa (WCA) includes three main steps: (i) packaging of T&Is ready to go, (ii) marketing of packaged T&Is, (iii) availing T&Is for large-scale adoption. Application of this approach is done using four main scaling strategies: (i) physical platforms (Market of Agricultural Innovations and Technologies: in-person meetings, Technologies parks and regional exchange of technologies), (ii) Online platforms (online MITA and FeSeRWAM), (iii) Innovation Platforms (IPs), (iv) Public-Private-Producers-Partnerships (PPPP). These scaling mechanisms are instrumental to accelerating the uptake and spillover of climate-smart agriculture innovations in WCA and beyond. To date, CORAF and partners have generated about 327 technologies that are under scaling process in the region by applying the aforementioned mechanisms. As part of the MITA in-person technologies market, CORAF convenes every year about 200 participants from 23 countries to discuss, exchange technologies and business opportunities. The online MITA (to date) displays 243 technologies and has recorded up to date about millions of views/visitors, with more than 10 recent intentions to purchase been analyzed. CORAF has set-up about 323 IPs and 4 PPPPs in different countries across the region to serve as drivers of dissemination of proven innovative technologies and practices.